Chapter 4 Compassion in primary and community healthcare - Hordern, Joshua (Taylor & Francis, 2017)
Compassion is an attribute of a person's affective understanding, which aims to enable, so far as possible, shared experiences of the world's ills and some alleviation of those ills' effects. Such an attribute is thus of great value within healthcare institutions such as general practices and other primary and community healthcare settings. It may characterise the people who participate in those institutions; or, it may not so characterise them. The appearance of compassion, under certain conditions and even in fragile and incomplete forms, is a kind of human excellence, a way of being for the good in community.* Compassion is not, therefore, a commodity, to be bought, sold and traded. Although time can be costed, there is no line for compassion in any budget. Were compassion to be thought a commodity, one could imagine trading it off against some more measurable factor (efficiency, cost-effectiveness, etc.). However, our human capacity for compassion, though fragile, tends to resist such marginalisation and reductionism.